Greater variability in daily physical activity is associated with poorer mental health profiles among obese adults. (March 2018) - Maher, Jaclyn P.; Huh, Jimi; Intille, Stephen; Hedeker, Donald; Dunton, Genevieve F.
Abstract: Research is inconclusive about whether physical activity (PA) should be performed every day or performed less frequently but in longer bouts to obtain mental health benefits. The current study examined the extent to which day-to-day variability in PA is associated with adults' mental health, and if this association differed by Body Mass Index (BMI). Adults (N = 116) completed three waves of data collection (each lasting 4 days) during which participants completed a questionnaire assessing mental health (life satisfaction, depressive symptoms, perceived stress), wore a waist accelerometer, and had height and weight measured. This study employed a novel two-stage data analysis approach using the standalone program MIXWILD. The first-stage model partitioned mean level as well as between-subject and within-subject variances in daily PA by estimating a random location (subject-level mean) and a random scale (subject-level variability) for daily PA. In the second-stage, these random subject effects for daily PA along with their interactions with BMI were used as predictors for subject-level mental health outcomes. Associations between subject-level variability in daily PA and mental health outcomes significantly differed depending on adults' BMI (life satisfaction: β = −0.05, p < 0.05; depressive symptoms: β = 0.03, p < 0.05; perceived stress: β = 0.04, p < 0.01). Greater day-to-day variability in PA was associated with poorer mental health in adults with higher BMI values as compared to adults with lower BMI. For individuals with high BMI values, inconsistent activity patterns may have consequences that diminish mental health. Strategies that promote consistency in daily PA may be useful for individuals with high BMI to enhance mental health. Highlights: Variability in physical activity was negatively associated with mental health among adults with high BMI values. These associations were consistent across multiple indicators of mental health. Promoting consistency in daily physical activity may be useful for individuals with high BMI values. Researchers should move beyond focusing solely on mean levels of constructs and consider subject-level variability.